Biocontrol of Rhizoctonia solani in cotton by fluorescent pseudomonads - and J.P. VERMA, G.S. LAHA, R.P. SINGH (Indian Phytopathology, 2002)
Isolates of fluorescent pseudomonads were tested for their ability to suppress the root rot and damping off pathogen of cotton, Rhizoctonia solani. Forty four per cent of the isolates suppressed the growth of the pathogen very strongly. The disease intensity was reduced from 52.6 per cent (with non - bacterized seeds) to zero (with seeds bacterized with isolates F-13, F-14 and F-11) in pot experiements.